2007
DOI: 10.1084/jem.20062545
|View full text |Cite
|
Sign up to set email alerts
|

Selective blockade of the inhibitory Fcγ receptor (FcγRIIB) in human dendritic cells and monocytes induces a type I interferon response program

Abstract: The ability of dendritic cells (DCs) to activate immunity is linked to their maturation status. In prior studies, we have shown that selective antibody-mediated blockade of inhibitory FcγRIIB receptor on human DCs in the presence of activating immunoglobulin (Ig) ligands leads to DC maturation and enhanced immunity to antibody-coated tumor cells. We show that Fcγ receptor (FcγR)–mediated activation of human monocytes and monocyte-derived DCs is associated with a distinct gene expression pattern, including seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 38 publications
3
81
0
Order By: Relevance
“…In B cells, FcγRIIB functions as a regulator of activating signals transmitted by the B cell receptor (BCR) 3 . In DC, the balance between activating and inhibitory FcγR activity influences their relative activation status 7 . In addition to hematopoietic cells, FcγR are expressed by follicular DCs, endothelial cells, microglial cells, osteoclasts and mesangial cells 3 .…”
Section: Fcγ Receptor Subtypes and Functionsmentioning
confidence: 99%
“…In B cells, FcγRIIB functions as a regulator of activating signals transmitted by the B cell receptor (BCR) 3 . In DC, the balance between activating and inhibitory FcγR activity influences their relative activation status 7 . In addition to hematopoietic cells, FcγR are expressed by follicular DCs, endothelial cells, microglial cells, osteoclasts and mesangial cells 3 .…”
Section: Fcγ Receptor Subtypes and Functionsmentioning
confidence: 99%
“…However, activation of various receptor-mediated pathways, such as downregulation of intracellular innate and adaptive antiviral mechanisms, could also contribute to enhanced dengue pathogenesis3. Activating FcγRs are known to signal through phosphorylation of immunoreceptor tyrosine-based activation motif (ITAM) and spleen tyrosine kinase (Syk)4. Activated Syk controls a number of pathways, including actin remodelling necessary for phagocytosis5 and STAT-1-dependent interferon-stimulated gene (ISG) induction independent of interferon receptor signaling4.…”
mentioning
confidence: 99%
“…The importance of the inhibitory FcγRIIB in regulating many IgG-mediated responses in different leukocytes was made evident in FcγRIIB-deficient mice, which showed enhanced activity of many IgG-mediated cell responses including: phagocytosis, immune complex-mediated inflammation, IgG- mediated passive and active anaphylaxis, and IgE-mediated anaphylaxis [42,43]. They also showed enhanced dendritic cell maturation, and antigen presentation [44][45][46]. These results thus confirmed that FcγRIIB regulates initiation of cell functions by generating, together with activating Fcγ receptors, a threshold for cell activation [31,47].…”
Section: Coexpression Of Fcγ Receptors and Threshold For Cell Activationmentioning
confidence: 95%